Femtosecond Pulse Propagation in a Highly Nonlinear Photonic Crystal Fiber - Gabayno, J. F.; Alonzo, C. A.; Garcia, W. O. (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Femtosecond pulses are launched into a highly nonlinear photonic crystal fiber (PCF). The input and output spectra were measured using a monochromator and streak camera. The spectrum of the output from a 50 cm PCF pumped at 794 nm for different pump powers features asymmetric side lobes due to intrapulse Raman scattering. Similar measurements on a 100 cm PCF pumped at 795 nm highlight the appearance of blueshifted peaks as a result of energy transfer of solitons to dispersive waves. Broadening in the spectrum is observed and attributed to Raman-scattering-induced soliton self-frequency shift. Spectrograms of both input and output pulses into a 50 cm PCF are captured using a streak camera. The spectrum reveals that individual modes observed on the spectrogram are actually a decomposition of the input pulse.